Biostimulants on mineral nutrition and fiber quality of cotton crop - Ricardo de A. Silva; Jerffson L. Santos; Luan S. Oliveira; Mauricio R. S. Soares; Saad M. S. dos Santos (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Biostimulants are used in cotton (Gossypium hirsutum L.) to balance vegetative and reproductive growth as well as to increase cotton seed yield and fiber quality. Therefore, in order to study the efficiency of seed treatment with biostimulants, nutrition, production and technological quality for the cotton fiber, a field experiment was installed. The study was conducted at the Alvorada farm research field, in Luis Eduardo Magalhães municipality - BA. The experiment was arranged in a completely randomized block design with four replicates and five treatments (control group, untreated group, Booster®, Stimulate®, Improver® and Biozyme®). Leaf contents of nutrients, yield and technological quality of the fiber were evaluated. The results showed that application of biostimulants in the seeds increased the N, K, S and Fe contents in the cotton leaf, but there was no influence on the crop yield. However, these products caused changes in the fiber characteristics, related to length uniformity, micronaire, length and strength of the fiber.